2020
DOI: 10.1515/jpm-2019-0402
|View full text |Cite
|
Sign up to set email alerts
|

Drug exposure during pregnancy and fetal cardiac function – a systematic review

Abstract: Background:The aim of this systematic review was to describe the effects of drug exposure during pregnancy on fetal cardiac function. Methods: We searched MEDLINE, Embase, Cochrane and SCOPUS for studies assessing fetal cardiac function in drug-exposed human pregnancies. Risk of bias was assessed by the Risk Of Bias In Non-randomized Studies of Interventions (ROBIN-I) tool. Results: We included 32 studies on eight different drug groups. They included 51 outcome variables, which were all based on ultrasound tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The most severe side effects of Ritodrine are the severe maternal side effects such as cardiac side effects, and even death. 44 Therefore, the future investigation has to be focused on the beneficial and side effects of Ritodrine on both endometrium and myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The most severe side effects of Ritodrine are the severe maternal side effects such as cardiac side effects, and even death. 44 Therefore, the future investigation has to be focused on the beneficial and side effects of Ritodrine on both endometrium and myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel is an antiplatelet agent that may sometimes be used with or instead of LDA to reduce cardiovascular risk. NICE guidance [40], four systematic reviews [16,[41][42][43] and a case report/review [44] evaluated LDA, NSAID and clopidogrel use in pregnancy.…”
Section: Nsaids and Anti-platelet Drugsmentioning
confidence: 99%
“…A systematic review of the effects of various drugs on foetal cardiac function evaluated by ultrasound found that all NSAIDs (including COX2 inhibitors) increased constriction in the ductus arteriosus, within 4–30 h of exposure and resolved by 72 h of discontinuation [ 43 ]. In this study the critical gestational age (measured for indomethacin) increased from 5–10% of foetuses at weeks 26–27 to 50% at week 32.…”
Section: The Guidelinementioning
confidence: 99%
“…Recommendations were based on NICE guidance [40], four systematic reviews [16,[41][42][43], a case report/review [44], UKTIS [18], LactMed [20] and United States Food and Drug Administration (FDA) guidance [45], as shown in Supplementary Tables S5 and S6, available at Rheumatology online.…”
Section: Nsaids and Anti-platelet Drugsmentioning
confidence: 99%